Public enterprise reforms in the United States and the People's Republic of China: a drift toward constitutionalization and departmentalization of enterprise management - Chan, Hon S.; Rosenbloom, David H. (2009)
Does globalization foster administrative convergence? Is that the case with public enterprise reform in the United States and the People's Republic of China? Few analyses compare public enterprise reform in the two countries because of their was differences in regulatory approaches, public policy, and government structure. This article contrasts how American and Chinese public enterprises are developed, defined, and managed, along with their emerging control infrastructures. This the resulting strengths and weaknesses. While vast differences remain apparent between the two countries, this essay provides insights into why those gaps persist, and may even continue to grow. - Reproduced.
Keywords: Administrative reform - United States; Administrative reform